Justifications of entitlement in grandiose and vulnerable narcissism: The roles of injustice and superiority. (1st January 2021) - Freis, Stephanie D.; Hansen-Brown, Ashley A.
Abstract: This research examines whether two people can be highly entitled but arrive at that conclusion in different ways. Using a lens of trait narcissism, we hypothesized that individuals high in grandiose narcissism (GN) justify entitlement via perceived superiority whereas individuals high in vulnerable narcissism (VN) justify entitlement via concerns of injustice. Participants across three studies (ns = 135–280) completed narcissism and entitlement measures. Study 1 participants selected domains (e.g., admiration, power) to which they felt entitled and indicated reasons why. Study 2 and 3 tested mediation models with measures of superiority (i.e. perceived status) and injustice (i.e. felt victimhood). We found that both narcissistic variants reported high entitlement. However, people high in GN justified their entitlement with perceived superiority (e.g. "I am naturally deserving") which mediated associations between GN and entitlement. In contrast, people high in VN justified their entitlement with concerns of injustice (e.g. "I have been disadvantaged in the past") which mediated associations between VN and entitlement. Three additional studies (ns = 78–243), reported in footnotes, replicated mediation models. This work furthers theoretical understanding on a core trait shared by the narcissistic variants and illuminates differences in how people justify deservingness. Highlights: Narcissistic subtypes' core of entitlement is differentially determined. People high in grandiose narcissism explain deservingness via perceived superiority. People high in vulnerable narcissism explain deservingness via concerns of injustice.